PENGARUH PENGUASAAN KOSAKATA DAN TATA BAHASA TERHADAP KEMAMPUAN MENULIS TEKS RECOUNT BAHASA INGGRIS - Yuni Istiqomah; Hasbullah Hasbullah (Universitas Indraprasta PGRI, 2021)
Abstract: This study aims to determine: The effect of vocabulary and grammar mastery on the English recount text writing skills of state junior high. The results of the hypothesis obtained the following conclusions: (1) There is a significant influence in mastering the vocabulary and grammar together on the ability to write English recount text in junior high school. This is shown from the value of Sig 0.010 <0.05 and Fh = 4.972. (2) There is a significant influence of vocabulary mastery on writing English recount text of state junior high school. This is shown from the value of Sig 0.033 <0.05 and th = 2192. (3) There is a significant influence of grammar mastery on writing English recount text of state junior high school. This is shown from the value of Sig 0.039 <0.05 and th = 2.111.Keywords: vocabulary, grammar, recount text